Jurassic World. Fallen kingdom [videorecording (Blu-Ray)] - Pratt, Chris, 1979-; Howard, Bryce Dallas, 1981-; Spall, Rafe, 1983-; Cromwell, James (Universal Pictures Home Entertainment, 2018)
It's been three years since the theme park and luxury resort was destroyed by dinosaurs out of containment. Isla Nublar now sits abandoned by humans while surviving dinosaurs fend for themselves in the jungles. When the island's dormant volcano begins roaring to life, Owen and Claire mount a campaign to rescue the remaining dinosaurs from this extinction-level event.